Inclusive regional value chains: blockchaining perishable agricultural products in Southern Africa - Sama, Hamisi K. (Logistics, supply chain, sustainability and global challenges, 2023)
In Southern Africa due to unsystematically and uncoordinated regional value chain (RVCs), plenty of perishable agricultural products are lost because of spoilage and poor postharvest system misaligning upstream and downstream partners. Although appeal for increasing trade in Southern Africa region may seem plausible, there are strictly speaking no well-grounded economic reasons why perishable agricultural products trade should be an obsession. Broad-based inclusive RVCs through blockchaining perishable agricultural products could enable far more effective responses to region’s sustainable developmental challenges as it does in developed and emerging economies. Recently, the rise and expansion of inclusive RVCs and emphasis on blockchain has spurred major paradigm shift on revamping postharvest system. The investigate relevance of blockchaining initiatives towards inclusive RVCs to perishable agricultural products in Southern Africa. Through a quantitative research approach involving quantitative data collection methods, the research aims to assess the current challenges, opportunities, and perceptions regarding blockchain technology in the agricultural sector. Study findings practically and empirically contribute to excel blockchain for supporting development of inclusive and resilient value chains, providing insights for policymakers and stakeholders in promoting sustainable economic growth in Southern Africa's agricultural sector.
Keywords: blockchain; inclusive regional value chain; perishable agricultural products; pokvarljivi kmetijski proizvodi; veriženje blokov; vključujoča regionalna vrednostna veriga